Влияние внешней среды на массовые и высотно-скоростные характеристики сверхлегких дистанционно пилотируемых летательных аппаратов (СДПЛА) - Котов, А. Б.; Таврин, В. А. (НТУ "ХПИ", 2011)
In the article were considered the basic questions of dependence from mass and height-speed descriptions SLWRCUA from the different environmental factors. The main problems were selected concerning of contraction of SLWRCUA in accordinance wish accounting modern ways of researches
Keywords: летательный аппарат; предельные возможности человеческого организма; погодные условия; нижний слой тропосферы; высота полета